Implementasi Pengelolaan Dana Infaq di Tpq Al-Hidayah Probolinggo - Fahad Abdul Aziz; Reza Hilmy Luayyin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The focus of education in Indonesia tends to be on formal education in schools. However, non-formal education also has an important contribution in forming a quality personality. One form of non-formal education is the Al-Qur'an Park (TPQ). The existence of this Al-Qur'an educational institution has a main mission, namely introducing and instilling Al-Qur'an values from an early age. The approach chosen by the researcher is a descriptive qualitative approach where data is collected directly in the field using observation, interview and documentation techniques to obtain data from informants regarding the implementation of management and infaq at TPQ Al-Hidayah Probolinggo. The result show that the implementation of fund management at TPQ Al-Hidayah is considered sufficient in carrying out TPQ operations because it is quite supported by infaq funds or community donations, but it is quite difficult to develop TPQ. Important factors in the implementation of infaq fund management at TPQ Al-hidayah are: aspects of public trust that are still lacking in institutional managers, the absence of integrated financial recording standards, the involvement of managers who are not yet very competent, Infaq or donations from the community are quite large, the allocation of funds is not yet on target, periodic evaluations have not been carried out, unclear internal regulations regarding fund management, lack of adaptation to digital technology, lack of innovation in management means that fund management is not yet accountable and professional.